Multi stage OTA design: From matrix description to circuit realization. (July 2018) - Biabanifard, Sadegh; Hosseini, S. Mehdi; Biabanifard, Mohammad; Asadi, Shahrouz; Yagoub, Mustapha C.E.
Abstract: This paper presents a comprehensive approach to frequency compensating multistage amplifiers. Different stage cases have been considered namely, differential voltage and current blocks, and general compensation blocks for both voltage and current states. Then, a matrix description has been proposed to describe the configurations. The approach involved binary matrixes in order to model amplifiers with feedback networks. Evolutionary algorithms were used to find optimum numerical values and simplify symbolic transfer functions. Also a diagram-based design was used to find the appropriate MOSFET DC bias conditions and dimensions. Note that using simplified transfer functions to symbolically locate the poles and zeroes allowed a better circuit design knowledge compared to numerical approaches. To demonstrate the proposed procedure, two circuit were designed in TSMC 0.18 μm CMOS technology and simulated results successfully compared to linear models extracted from the matrix description. According to simulations, the proposed configurations in both voltage and current states show excellence performance versus previous works. Finally, special design cases such as multi-compensation blocks and N-stage approach were discussed. Graphical abstract: